2022
DOI: 10.1111/anae.15684
|View full text |Cite
|
Sign up to set email alerts
|

Glycated haemoglobin and the risk of postoperative complications in people without diabetes: a prospective population‐based study in UK Biobank

Abstract: Summary The aim of our study was to clarify the association between glycated haemoglobin (HbA1c) and postoperative outcomes in people without an existing diagnosis of diabetes. Half a million adults were recruited into the UK Biobank prospective cohort study between March 2006 and October 2010. We divided participants into three groups: no diagnosis of diabetes and HbA1c < 42 mmol.mol−1; no diagnosis of diabetes and elevated HbA1c (≥ 42 mmol.mol−1 with no upper limit); and prevalent diabetes (regardless of HbA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…Our data are in line with recently published data from a UK Biobank study looking at the relationship between HbA 1c and the risk of postoperative complications in all forms of surgery. Those authors showed that, whilst the unadjusted risk of an adverse post-operative event was significant (OR [95% CI] 1.43 [1.02-2.02]; [18]. Diabetes causes macrovascular and microvascular complications, namely myocardial infarction, stroke, and renal, nerve and eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in line with recently published data from a UK Biobank study looking at the relationship between HbA 1c and the risk of postoperative complications in all forms of surgery. Those authors showed that, whilst the unadjusted risk of an adverse post-operative event was significant (OR [95% CI] 1.43 [1.02-2.02]; [18]. Diabetes causes macrovascular and microvascular complications, namely myocardial infarction, stroke, and renal, nerve and eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Public Health England has estimated the prevalence of elevated HbA 1c levels without a formal diagnosis of (pre-) diabetes in the general population to be 13%, of which 2.3% will meet the diagnosis of diabetes [15]. Lam et al found a prevalence of elevated HbA 1c levels in only 5% of their study population, probably because the Biobank database represents a relatively young sample of the general population and not a surgical population [7]. The prevalence of elevated HbA 1c levels in the population presenting for surgery could be as high as 40% [1], meaning that a significant proportion of adult patients presenting for surgery may have an increased risk of postoperative complications.…”
Section: Hba 1c and Postoperative Complicationsmentioning
confidence: 99%
“…To summarise, the study by Lam et al. [7] shows us that a substantial proportion of patients presenting for surgery have a higher risk of postoperative complications related to long‐term glycaemic control, also in HbA 1c ranges not diagnostic for diabetes. The association is largely driven by the presence of comorbidities, especially in patients with pre‐diabetes.…”
Section: Possible Interventionmentioning
confidence: 99%
See 2 more Smart Citations